2020
DOI: 10.3390/app10155264
|View full text |Cite
|
Sign up to set email alerts
|

Thermometry in a Multipole Ion Trap

Abstract: We present a characterization of the ions’ translational energy distribution in a multipole ion trap. A linear mapping between the energy distribution of the trapped ions onto the ions’ time-of-flight (TOF) to a detector is demonstrated. For low ion temperatures, a deviation from linearity is observed and can be attributed to the emergence of multiple potential minima. The potential landscape of the trapped ions is modeled via the finite element method, also accounting for subtleties such as surface-charge acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…A common 22-pole trap configuration was used initially and is described elsewhere. We have seen anomalous heating effects in this trap which we partly attribute to patch potentials from the trap rods . To minimize this effect and to improve optical access and increase experimental versatility, we constructed a 16-pole trap with 100 μm diameter wires as the RF trapping electrodes based on previous developments in our group, henceforth termed the wire trap. The wire trap replaced the 22-pole trap in the experimental apparatus, and reaction rate experiments were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…A common 22-pole trap configuration was used initially and is described elsewhere. We have seen anomalous heating effects in this trap which we partly attribute to patch potentials from the trap rods . To minimize this effect and to improve optical access and increase experimental versatility, we constructed a 16-pole trap with 100 μm diameter wires as the RF trapping electrodes based on previous developments in our group, henceforth termed the wire trap. The wire trap replaced the 22-pole trap in the experimental apparatus, and reaction rate experiments were repeated.…”
Section: Methodsmentioning
confidence: 99%
“…The benefits of using a MIT for buffer gas cooling of molecular and atomic ions on the ∼K-mK level has been extensively explored [53][54][55]. It has been shown that an increased number of trap poles minimises rf heating effects, allowing more efficient buffer gas cooling than would otherwise be achievable, as well as stable cooling of systems with a smaller ion-atom mass ratio than is possible in quadrupole traps [56,57].…”
Section: Multipole Ion Trapmentioning
confidence: 99%
“…A mass-selected ensemble of hydroxyl anions OH − formed via electron attachment is loaded into an octupole radio-frequency wire trap, as schematically shown in Figure 2a and described in detail in [39,40]. Multipole ion traps feature a large field-free region in the radial direction, thus reducing radio-frequency heating [41].…”
Section: Measurement Of Reaction Rate Coefficientsmentioning
confidence: 99%
“…The kinetic temperature is set to 355(10) K, via collisions with a pulse of helium buffer gas. The temperature of the ions is measured by mapping the ions' energy distribution to their time-of-flight (TOF) to the detector [40]. The ions' spatial distribution is mapped out by photodetachment tomography with a far-threshold laser [42].…”
Section: Measurement Of Reaction Rate Coefficientsmentioning
confidence: 99%